The Voice of Indonesian Migrant Workers Abroad: How is the Legal Assistance for Them? - Uluwiyah, Fatimatul (The Indonesian Journal of International Clinical Legal Education, 2021)
Indonesian Migrant Workers who work abroad often receive treatment that is not in accordance with what was agreed upon, during the validity period of the employment contract, Indonesian Migrant Workers or abbreviated as TKI do not get their rights as workers, and often receive bad treatment such as persecution in the form of physical. In its development, several existing cases have been found, such as several female workers working in Saudi Arabia who have experienced bad treatment, either in the form of sexual abuse or harassment by their employers, besides that in the country, there are many TKI and TKW who receive bad treatment and violations of their rights. The problems raised in this research consist on what are the requirements and procedures for submitting and providing legal assistance for Indonesian migrant workers abroad, and how is the Government's response in providing legal assistance to migrant workers.